Demografie und Ungleichheit: der Einfluss von Veränderungen der Haushaltsstruktur auf die Einkommensverteilung in Deutschland - Andreas Peichl; Nico Pestel; Hilmar Schneider (Institute for the Study of Labor (IZA), 2009)
In Germany, two observations can be tracked over the past 15 to 20 years: First, income inequality has constantly increased while, second, the average household size has been declining dramatically. The analysis of income distribution relies on equivalence-weighted incomes, which take into account household size. Therefore, there is an obvious link between these two developments. The aim of the paper is to quantify how the trend towards smaller households has influenced the change in income inequality. It appears that inequality would also have increased without this demographic trend. But its level would be noticeably lower than it actually is.
urn:nbn:de:101:1-20090615125
Keywords: D31; D63; I30; J11; 330; Demography; income inequality; inequality decomposition; household structure; SOEP; Germany; Einkommensverteilung; Privater Haushalt; Sozialer Wandel; Deutschland